2002
DOI: 10.1055/s-2002-32840
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss resterilisierter Kunststoffnetze aus Polypropylen auf das Wachstum humaner Fibroblasten - Eine experimentelle in vitro Studie -

Abstract: Resterilized meshes inhibit growth of human fibroblats in vitro significantly, demonstrated by a reduced proliferative activity and an increased apoptotic index. This could be caused by a release of toxic substances from the meshes, which have a negative influence on cell growth. Therefore, resterilization cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There have been few studies that have evaluated the effects of EO sterilisation on the proliferation of fibroblasts cultured on surgical meshes. Autoclave sterilisation at 121 °C, which is used to sterilise some LCM in the developing world, appears to impact the proliferation of fibroblasts, as reported by Broll et al [ 19 ]. Savaris et al [ 27 ] examined the biocompatibility of polylactic acid films after EO sterilisation with fibroblasts in vitro and after implantation in vivo, without finding any toxic effect in either study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There have been few studies that have evaluated the effects of EO sterilisation on the proliferation of fibroblasts cultured on surgical meshes. Autoclave sterilisation at 121 °C, which is used to sterilise some LCM in the developing world, appears to impact the proliferation of fibroblasts, as reported by Broll et al [ 19 ]. Savaris et al [ 27 ] examined the biocompatibility of polylactic acid films after EO sterilisation with fibroblasts in vitro and after implantation in vivo, without finding any toxic effect in either study.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding in vitro evaluations of LCM, few studies have considered the biocompatibility of LCM towards cells. Sanders et al compared the adherence of bacteria on autoclaved LCM and commercially available meshes and found no significant difference between the two types, confirming their safety for human implantation [ 19 ]. Our previous study evaluated the in vitro biocompatibility of LCM using HDFs and reported high proliferation and attachment to LCM, which is now additionally confirmed on EO-sterilised LCM [ 20 ].…”
Section: Discussionmentioning
confidence: 99%